Objective assessment of dysarthric disorders in patients with multiple sclerosis depending on sex, age, and type of text read - Warmbier, Wojciech A.; Popiel, Małgorzata; Guzik, Agnieszka; Drużbicki, Mariusz; Bartosik-Psujek, Halina (Frontiers in Neurology, 2023)
Purpose To assess dysarthric disorders in multiple sclerosis (MS) patients in comparison with healthy individuals and MS patients without dysarthria depending on the patient’s sex, age, and the type of text read using an objective tool. Methods The study was carried out in a group of 72 persons, including 24 with MS presenting dysarthria (study group) and 24 healthy individuals (healthy control group), and 24 with MS without dysarthria (MS control group). Performance (reading) time was evaluated by means of an objective tool created for the purpose of the analysis. Results The study showed significant statistical differences in the analyzed performance time of: poetry reading, prose reading, and completing a diction exercise, among persons with MS from the study group presenting dysarthria and both control groups (p < 0.05). It took more time to read the poem, and prose and to perform a diction exercise in the study group with dysarthria than in both control groups (with no significant differences between the two) Similarly, the comparison between the groups in terms of sex and age showed disturbances in the above-mentioned parameter in the study group. What was not demonstrated were significant differences in the evaluated speech parameters depending on both sex and age separately in the group of MS patients with dysarthria, and both control groups (p < 0.05). Conclusion The objective tool created for the purpose of speech analysis is useful in detecting discrepancies in performance (reading) time among MS patients with dysarthria, and healthy individuals, as well as patients with MS without dysarthria and can be used in clinical practice for diagnostic purposes, however, further research is essential to complete its validation.